The impact of the coronavirus disease 2019 pandemic on physical activity in U.S. children - Kirsten Tulchin-Francis; Wilshaw Stevens, Jr; Xiangli Gu; Tao Zhang; Heather Roberts; Jean Keller; Dana Dempsey; Justine Borchard; Kelly Jeans; Jonathan VanPelt (Elsevier, 2021)
Background: Daily moderate-to-vigorous physical activity (MVPA) is vital to the physical, mental, and social well-being of children. Early restrictions during the coronavirus disease 2019 (COVID-19) pandemic included the closure of schools and physical activity (PA) amenities across the US. This study aimed to examine the impact of the pandemic on the PA and play behavior of U.S. children and to provide evidence-based recommendations to improve their PA. Methods: A cross-sectional, online, parent-reported survey was conducted of children aged 3-18 years between April and June 2020 to assess light PA and MVPA using a modified Godin Leisure-Time Exercise Questionnaire. Additional items included family/child socioeconomic demographics, child adaptability to the pandemic, and community access. The survey was shared through social media and snowball sampling distribution. Results: Analysis of 1310 surveys indicated child PA scores declined significantly during the pandemic (from 56.6 to 44.6, max 119, p < 0.001). Specifically, MVPA score decreased (from 46.7 to 34.7, max 98, p < 0.001) while light PA remained the same. Age-based changes were seen in the quantity, variety, and intensity of PA, with the lowest pandemic-related impact seen in preschoolers and the highest in high schoolers (-4.7 vs. -17.2, p < 0.001). Community-based peer PA decreased across all age groups. Conclusion: This study shows decreased PA levels in U.S. children, according to parent reporting, during the COVID-19 pandemic. Recommendations for community leaders, educators, and parents to improve PA in children are provided. With continued spread of COVID-19, these results and recommendations may be imperative to the physical well-being of U.S. children.